ChemInform Abstract: Organocatalytic Domino Reactions: Synthesis of Densely Functionalized Cyclohexene Derivatives. Issue 46 (18th November 2014) - Bi, Bo; Ding, Yuyang; Lou, Qinxin; Hu, Wenhui; Chan, Albert S. C.; Song, Hongrui; Zhao, Junling
Abstract The domino reaction of hexanal derivative (I) with α, β‐unsaturated aldehydes proceeds in the presence of a chiral diphenylsilylprolinol catalyst under mild conditions to give cyclohexene derivatives in good yields and with high enantioselectivities.